Research on Dynamic Equalization of Optical Power for Satellite-Ground Laser Communication - Yuefeng CAI; Haifeng LIU; Bo LIU; Wei LIN (天地一体化信息网络)
Aiming at the problem of light intensity scintillation caused by atmospheric turbulence at the receiver of satellite-ground laser communication will aff ect the communication quality, an optical power balance system based on gain competition was studied.The experiment verifi ed that the received power fl uctuation increased the communication bit error rate.The static output curve of the equalization system under gain competition was studied and the equalization performance of the dynamic time domain signal was tested.The experimental results showed that the system could compress the power fl uctuation range of the dynamic signal to 4 dB.